2007
DOI: 10.1098/rsbl.2007.0005
|View full text |Cite
|
Sign up to set email alerts
|

Intense ultrasonic clicks from echolocating toothed whales do not elicit anti–predator responses or debilitate the squid Loligo pealeii

Abstract: Toothed whales use intense ultrasonic clicks to echolocate prey and it has been hypothesized that they also acoustically debilitate their prey with these intense sound pulses to facilitate capture. Cephalopods are an important food source for toothed whales, and there has probably been an evolutionary selection pressure on cephalopods to develop a mechanism for detecting and evading sound-emitting toothed whale predators. Ultrasonic detection has evolved in some insects to avoid echolocating bats, and it can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 14 publications
(27 reference statements)
2
33
0
Order By: Relevance
“…Such a system will not work against echolocating toothed whales, but different body compositions with varying muscle mass and hard parts inevitably provide squid species with different capabilities to passively avoid biosonar detection or actively escape from capture attempts (Wilson et al 2007). Squid with high muscle content will present a strong sonar target and a high potential energy return for an echolocating predator (Clarke et al 1985), but the muscle will also potentially enable the squid to evade an approaching toothed whale (via jet escape), which in turn may invest more energy in pursuit and capture.…”
Section: Discussionmentioning
confidence: 99%
“…Such a system will not work against echolocating toothed whales, but different body compositions with varying muscle mass and hard parts inevitably provide squid species with different capabilities to passively avoid biosonar detection or actively escape from capture attempts (Wilson et al 2007). Squid with high muscle content will present a strong sonar target and a high potential energy return for an echolocating predator (Clarke et al 1985), but the muscle will also potentially enable the squid to evade an approaching toothed whale (via jet escape), which in turn may invest more energy in pursuit and capture.…”
Section: Discussionmentioning
confidence: 99%
“…For marine invertebrates, our knowledge of hearing capabilities is relatively poor and a definition or even certainty of sound detection is not agreed upon (Webster et al 1992) despite their magnitude of biomass and often central role in ocean ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…While early anecdotal evidence suggested that squid may 61 respond behaviorally to sound (Dijkgraaf 1963;Maniwa 1976), stunning or predator avoidance 62 responses to odontocete echolocation clicks have been hypothesized, debated and not-verified 63 (Norris and Møhl 1983; Wilson et al 2007). More recent work has largely focused on anatomical 64 and physiological investigations.…”
mentioning
confidence: 99%